Student-Life Stress Level and its Related Factors among Medical Students of Hamadan University of Medical Sciences in 2015 - Roya Nikanjam; Majid Barati; Saeed Bashirian*; Mohammad Babamiri; Ali Fattahi; Alireza Soltanian (Hamadan University of Medical Sciences, 2016)
Background and Objectives: Student-life stress can lead to various negative consequences such as physical illness, mental disorders or exhaustion. The present study was conducted to evaluate the level of student life stress and its related factors among medical students of Hamadan University of Medical Sciences. Materials and Methods: This cross-sectional study applied multistage random sampling to select 500university students at Hamadan University of Medical Sciences during 2015. The data collection tool used in this study was a self-report questionnaire containing two parts: a section on subjects' demographic details and another section for Student-Life Stress Inventory (SLSI). Data were analyzed in SPSS20-using descriptive and inferential statistics, such as independent t-test, Pearson's correlation test and one-way ANOVA. Results: This study revealed that %57of the students had moderate levels of stress. The most important stressors included self-impose and pressure, and also the most important reactions to stressors included cognitive appraisal and emotional reactions, respectively. There was a significant association between exam stressors and branch, educational level, and mother's and father's education level (P< 0.05). Conclusions: According to the high level of stress in students and the recognition of demographic factors, effective educational interventions can be conducted to reduce stress.